2020
DOI: 10.1186/s12887-020-02254-y
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between vitamin a status and refractory Mycoplasma Pneumoniae pneumonia (RMPP) incidence in children

Abstract: Background: Vitamin A plays a pivotal role in respiratory infection, accurate estimation of vitamin A status was recommended in planning and implementing interventions. As infections affect serum vitamin A productions, the real status need to be adjusted by acute phase protein (APP). Mycoplasma pneumoniae is an important cause of respiratory infection in children, the association between vitamin A concentrations and refractory Mycoplasma pneumoniae pneumonia (RMPP) remains unclear. Methods: 181 MPP patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…In a cross-sectional study performed by Abd El-Shaheed et al (2018) reported that there was a positive association between vitamin A and both CD4 and Tβ4, thus, vitamin A deficiency reduced the efficacy of the immunity system against infectious diseases. In another clinical trial, it was reported that vitamin A intervention caused a decrease in the duration of fever and hospital stay ( Li et al, 2020a ). In terms of hospital stay, we found that the interventions with zinc or vitamin A reduced days of hospitalization by an average of 3.21 days (95% CI: 5.01–−1.41, p < 0.01) and 2.43 days (95% CI: 4.29–−0.57, p = 0.01), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In a cross-sectional study performed by Abd El-Shaheed et al (2018) reported that there was a positive association between vitamin A and both CD4 and Tβ4, thus, vitamin A deficiency reduced the efficacy of the immunity system against infectious diseases. In another clinical trial, it was reported that vitamin A intervention caused a decrease in the duration of fever and hospital stay ( Li et al, 2020a ). In terms of hospital stay, we found that the interventions with zinc or vitamin A reduced days of hospitalization by an average of 3.21 days (95% CI: 5.01–−1.41, p < 0.01) and 2.43 days (95% CI: 4.29–−0.57, p = 0.01), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, early identification and diagnosis of RMPP is a major problem that clinicians need to solve urgently. Some studies have shown that CRP, LDH, ESR, neutrophils (%), and lymphocytes (%) are predictive factors for RMPP [ 5 7 ], but it is contradictory that some studies have found no difference for these factors in RMPP and NRMPP [ 8 , 9 ]. In addition, we have also found that a large-scale dense consolidation shadow of the lungs occurs in the RMPP population, which may also be one of the predictive factors for RMPP [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Severe MPP can cause multisystem damage. In severe cases, respiratory and heart failure, and possibly death, may occur 4 , 5 . The pathogenesis of wheezing triggered by MP is complex, including autoimmune diseases, genetics, and environmental factors.…”
Section: Introductionmentioning
confidence: 99%